Religious Materiality in Elizabethan Essex (1558-1603) - Gomulkiewicz, Abigail (Material religion, 2020)
Based on an analysis of over 11,000 Elizabethan Essex wills, this article presents the first systematic study of the everyday religious environment of Essex. While scholars of the English Reformation increasingly study the everyday behaviors, routines, and rituals which defined English Protestant life, this article articulates how smaller household objects expand our knowledge of religion, practice, and remembrance in post-Reformation England. It also reinvestigates the potential for using wills as a foundation for the study of objects. This, in turn, helps us better understand and appreciate the substantial role objects had as part of an English Protestant religious identity increasingly built around remembrance and memory and, more broadly, enables us to question our historiographical assumptions about the speed, spread, and efficiency of the Reformation.